2021
DOI: 10.3389/fpsyg.2020.571124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Group Art Therapy Using Traditional Chinese Materials on Self-Efficacy and Social Function for Individuals Diagnosed With Schizophrenia

Abstract: The purpose of this study was to examine the effect of group art therapy using traditional Chinese materials on improving the self-efficacy and social function of individuals diagnosed with schizophrenia. In China, little research has been conducted on patients to measure the effectiveness of group art therapy, especially using traditional Chinese materials. To address this research gap, 104 individuals diagnosed with schizophrenia were tested in a group art therapy program that included 30 treatment sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…Moreover, the effects of calligraphy activity on cognition and attention are consistent with prior research on people with schizophrenia as systematically reviewed and meta-analyzed by Chu et al 6 The positive effects of calligraphy activity on cognition and attention may further explain the study findings that indicated the effects of calligraphy activity on self-efficacy and social functioning among people with schizophrenia. 28 However, the effects of calligraphy activity did not outperform occupational therapy, the intervention received by the TAU group in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Moreover, the effects of calligraphy activity on cognition and attention are consistent with prior research on people with schizophrenia as systematically reviewed and meta-analyzed by Chu et al 6 The positive effects of calligraphy activity on cognition and attention may further explain the study findings that indicated the effects of calligraphy activity on self-efficacy and social functioning among people with schizophrenia. 28 However, the effects of calligraphy activity did not outperform occupational therapy, the intervention received by the TAU group in the present study.…”
Section: Discussioncontrasting
confidence: 65%
“…Art-based therapies in China have improved patients' mental and emotional wellbeing. A patient with schizophrenia benefit from group art therapy incorporating traditional Chinese objects because it increases their sense of competence and social functioning, decrease their difficulties with these areas of functioning, and enhances their overall quality of life ( 76 ). Promoting older individuals' health can be aided through social engagement, a crucial active living component.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Employing mediums like painting, music, dance and games, GATs focus on the composition and interaction of group members to boost mental wellbeing. [19][20][21] Certain studies affirm the significant impact of GATs on the social functioning deficits, 22 sense of pleasure, 23 self-efficacy 24 and interpersonal relationships 25 of individuals with schizophrenia. The therapeutic benefits stem partly from the diverse artistic mediums that redirect patients' focus to the process of creation, helping to alleviate anxiety and stress, thus facilitating emotional expression and ameliorating the presentation of positive symptoms.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%